Orlistat ameliorates lipid dysmetabolism in high-fat diet-induced mice via gut microbiota modulation - Chengyan Huang; Yuanhui He; Ping Chai; Zongxin Liu; Sirui Su; Yanhui Zhang; Yuelan Luo; Shuiping Fu (Frontiers in Microbiology, 2025)
Orlistat reduces obesity by inhibiting gastrointestinal lipases, thereby blocking the absorption and accumulation of triglycerides in the intestine. It has been shown to improve lipid metabolism and alter intestinal microbial communities in animals and humans. However, the impact of Orlistat-induced changes in gut microbiota on obesity requires further investigation. In this study, we found that Orlistat significantly improved metabolic disorders, inhibited fat accumulation, and reshaped the structure of intestinal microbiota. Specifically, it reduced α diversity and increased the relative abundance of Verrucomicrobia and Akkermansia. Notably, antibiotic-induced gut microbiota depletion significantly weakened Orlistat’s effect on improving metabolic disorders. Furthermore, microbiota transplanted from Orlistat-treated mice effectively alleviated lipid metabolic disorders caused by a high-fat diet. We also observed that Orlistat increased food intake in mice and inhibited the synthesis of appetite-regulating hormones glucose-dependent insulinotropic polypeptide (GIP) and glucagon (Gcg). However, antibiotic-depleted microbiota mitigated this inhibitory effect. Interestingly, although Orlistat altered the gut microbiota of mice, transplanting these microbiota did not inhibit the synthesis of appetite-regulating hormones. In summary, our results suggest that Orlistat can reshape the gut microbiota, and the altered gut microbiota works synergistically with Orlistat to improve metabolic disorders. This improvement is related to the increased abundance of Verrucomicrobia and Akkermansia.